Построение и исследование нелинейной дифференциальной модели двухфазных сред - Скопецкий, В.В.; Марченко, О.А.; Самойленко, Т.А. (Кибернетика и системный анализ, 2010)
Сформульовано початково-крайову задачу для нелінійної системи одного параболічного рівняння вологопереносу–фільтрації та двох гіперболічних рівнянь теорії пружності. Отримано оцінки швидкості збіжності для неперервного за часом і повністю дискретно наближених розв’язків відповідної узагальненої задачі, побудованої за методом Гальоркіна. An initial–boundary-value problem for a nonlinear system of one moisture-transfer or filtration parabolic equation and two hyperbolic equations from the theory of elasticity is analyzed. The rate of convergence is estimated for a time-continuous and a completely discrete approximate solutions of the corresponding generalized problem set up by the Galerkin method.